2023
DOI: 10.1007/s40744-023-00535-3
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic Arthritis in Males and Females: Differences and Similarities

Abstract: Objective: To assess any differences and similarities in psoriatic arthritis (PsA) between sexes. Any possible differences of psoriasis and its potential impact on disease burden between sexes with PsA were also evaluated. Methods: Cross-sectional analysis of two longitudinal PsA cohorts. The impact of psoriasis on the PtGA was evaluated. Patients were stratified in four groups based on BSA. The median PtGA was then compared between the four groups. Moreover, a multivariate linear regression analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In our population, the prevalence of fibromyalgia in PsA patients reflects what is reported in the literature, even though prevalence rates may vary when using different criteria or tools for fibromyalgia detection (40,41) (43)(44)(45). To the best of our knowledge, there are very few studies reporting comorbidity impact on bDMARDs withdrawal in PsA.…”
Section: Original Papersupporting
confidence: 72%
“…In our population, the prevalence of fibromyalgia in PsA patients reflects what is reported in the literature, even though prevalence rates may vary when using different criteria or tools for fibromyalgia detection (40,41) (43)(44)(45). To the best of our knowledge, there are very few studies reporting comorbidity impact on bDMARDs withdrawal in PsA.…”
Section: Original Papersupporting
confidence: 72%
“…This study aimed to assess the Psoriasis Area and Severity Index (PASI) score and its correlation with liver function test (LFT) values in 102 psoriasis patients, with an average age of 44.81 ± 11.10 years and the study population comprised predominantly males (74.5%), with females accounting for 25.5% of the participants. In the comparison of this study Lubrano E et al 15 reported that the males were 51.8% and females were 48.2% with an overall mean age of 55.68+12.43 years. Consistently, in a study conducted by Sultan N et al 16 also it was reported that out of 140 patients, 87 (62%) were male and 53 (38%) were female, with a mean age of 40.97 ± 14.74 years.…”
Section: Discussionmentioning
confidence: 48%
“…Some studies suggest that males with PsA may experience more severe joint inflammation and damage, leading to increased disability and functional impairment. Females, on the other hand, may be more likely to report higher levels of pain, fatigue, and psychological distress associated with PsA [40]. However, these findings are not consistent across all studies, and further research is needed to fully elucidate the gender-specific differences in disease severity.…”
Section: Evaluation Of Eventual Gender Differences In Tmd-psamentioning
confidence: 93%
“…Males tend to present with more peripheral joint involvement, such as inflammation of the larger joints, including the knees, ankles, and wrists. On the other hand, females often exhibit a higher prevalence of axial involvement, which includes the spine, sacroiliac joints, and TMJ [40]. The reasons for this variation in joint involvement patterns between genders are not well understood and may be influenced by both hormonal and genetic factors.…”
Section: Evaluation Of Eventual Gender Differences In Tmd-psamentioning
confidence: 99%